2013
DOI: 10.1063/1.4793419
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire-filled polymer composites with ultrahigh thermal conductivity

Abstract: Realizing high thermal conductivity nanocomposites is a challenge because of difficulties in incorporating high fractions of uniformly dispersed nanofillers and countering low filler-matrix interfacial conductance. Here, we obviate these issues by using <3 vol. % gold nanowire fillers to obtain a 30-fold increase in polydimethylsiloxane thermal conductivity that is 6-fold higher than any nanocomposite at low nanofiller loadings and exceeds theoretical predictions. The nanowire diameter and aspect ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 26 publications
3
51
0
Order By: Relevance
“…While metals are sometimes described as bad fillers due to low TC of their composites compared with other fillers , it should be noted that in most of the reported experiments, the metals were powders, likely more or less spherical shaped, thus possessing a low AR. Nikhil et al showed that composites with gold nanofibers can display a TC of 5 W m −1 K −1 , even at filler amounts as low as 3 m%. Park et al indicated that by changing the shape of copper from sphere‐like to flake‐like an increase in TC can be noticed as well.…”
Section: Relevance Of Materials Propertiesmentioning
confidence: 99%
“…While metals are sometimes described as bad fillers due to low TC of their composites compared with other fillers , it should be noted that in most of the reported experiments, the metals were powders, likely more or less spherical shaped, thus possessing a low AR. Nikhil et al showed that composites with gold nanofibers can display a TC of 5 W m −1 K −1 , even at filler amounts as low as 3 m%. Park et al indicated that by changing the shape of copper from sphere‐like to flake‐like an increase in TC can be noticed as well.…”
Section: Relevance Of Materials Propertiesmentioning
confidence: 99%
“…Both particle–matrix ( R pm ) and particle–particle interfaces ( R pp ) contribute to R b , but the limiting thermal boundary resistance shifts from R pm to R pp when significant percolating networks are established and particle–particle contact is significantly increased . Furthermore, R pp can be reduced when using silver fill particles through welding or mechanical sintering . These processes are enabled by the soft, nearly oxide‐free silver surfaces and can lead to a 40‐fold improvement in k c .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Moreover, metallic particles 40 were introduced in carbon/polymer composites to develop conducting pathways in addition to those by carbon fillers, thereby improving the TC. 6,7,13,14,[19][20][21][22][23][24][25][26][27][28] For example, individual dispersion of fillers in the polymer matrix is necessary but insufficient for high TC composites since each filler was completely covered with polymer chains, rendering it 50 very difficult to transfer heat. S1 †).…”
Section: Introductionmentioning
confidence: 99%